Dissecting Gains from Trade: Changes in Welfare Cost of Autarky - Paras Kharel (East Asian Economic Review (EAER), 2018)
Amid a general rise in protectionism and a trade war between the world's two largest economies, this paper analyzes changes in gains from trade for the world over a decade marked by rapid global economic integration preceding the global financial crisis of 2007-08. It employs state-of-the-art quantitative trade models based on the gravity equation to estimate autarky gains from trade, as well as a recently introduced ANOVA-type structural estimation of the gravity equation to obtain trade costs free of residual trade cost bias. Between 1995 and 2006, the cost of moving to autarky increased by about 45% on average. A decomposition exercise suggests most of the increase in autarky gains from trade on average was due to increases in import shares in total spending, with a limited role for reallocations of spending across sectors with varied trade elasticities. Changes in trade costs between 1995 and 2006 are found to have increased autarky gains from trade, as measured in 2006, by up to 100%.
Keywords: F11; F12; F13; F14; F60; 330; Trade Costs; Gravity Model; Welfare; Gains from Trade; Globalization